Correction and optimization of a T2‐based approach to map blood oxygenation in small cerebral veins. Issue 3 (4th April 2015) - Krishnamurthy, Lisa C.; Mao, Deng; King, Kevin S.; Lu, Hanzhang
Abstract : Purpose: Cerebral venous blood oxygenation (Yv ) is an important biomarker in brain physiology and function. The present study proposes a procedure to provide a quantitative map of the brain's intravascular Yv . Theory and Methods: The method is based on a pulse sequence, T2 ‐Relaxation‐Under‐Phase‐Contrast (TRU‐PC) MRI, with postprocessing approaches to correct eddy‐current effects. A complete scan protocol consists of four TRU‐PC scans sensitized to large and small vessels with anterior–posterior and foot–head flow‐encoding directions, and the data are analyzed conjunctively. Eddy‐current correction was performed by fitting the tissue phase to a hyperplane, and then subtracting the eddy‐current phase from the measured vessel phase. The reproducibility of the Yv ‐maps was examined in five participants. Sensitivity of the Yv map to a caffeine challenge was studied in another five participants. Results: Removal of eddy‐current induced artifact allowed for the correction of T2 measurements, as demonstrated in vivo and with simulation. A Yv ‐map depicting all vessels in the slice can be obtained with the proposed protocol. Test–retest variability of the Yv ‐map was 3.7 ± 1.2%. Yv reduction can be reliably detected ( P < 0.001) following the caffeine ingestion. Conclusion: With the proposed TRU‐PC protocol and eddy‐current correction procedure, an accurate, vessel‐specific Yv map of the human brain can be obtained. Magn Reson Med 75:1100–1109, 2016. © 2015 Wiley Periodicals, Inc.